Comparison of Corrosion Behaviors of Bare Ti and TiO2 - Ali Döner (Emerging Science Journal, 2019)
In this study, titanium (Ti) surface was anodized by applying 60 voltages for two hours to form titanium dioxide (TiO2) with anodization method. After anodization procedure, comparison of corrosion behaviors of the bare titanium and TiO2 coated titanium was examined in 1 M KOH solution by using electrochemical methods such as anodic and cathodic current-potential curves and electrochemical impedance spectroscopy (EIS). Cyclic voltammetry (CV) and energy dispersive X-ray (EDX) were used to characterize bare Ti and anodically formed TiO2 surfaces. According to obtained results, Ti surface was smooth and compact. However, surface structure of TiO2 coated titanium was porous and nanotubes formed on the surface. This porous structure which has protective layer contributed to increase the corrosion resistance. Higher polarization resistance was obtained on porous TiO2 than that of bare titanium. Besides, this protective layer bore well against the alkaline corrosion during long-term immersion.